Identifying weather patterns responsible for renewable energy droughts over India - I. Dijkstra; H. C. Bloomfield; K. M. R. Hunt; K. M. R. Hunt (Advances in Geosciences)
Energy systems across the globe are evolving to meet climate mitigation targets. This requires rapid reductions in fossil fuel consumption and significant uptake of renewable generation. Renewable energy sources are weather-dependent, causing production to vary at timescales from minutes to decades ahead. A consequence of this variability is that there will be periods of low renewable energy production, here termed renewable energy droughts. This energy security challenge needs to be addressed to ensure grid stability. India is chosen as a study area as it is a region that has both a large proportion of renewable generation and good subseasonal predictability.